Optimalisasi Manajemen Parkir Pelabuhan Melalui Intelligent Transport System (ITS) Untuk Peningkatan Pelayanan Transportasi Dan Kepuasan Pengguna Jasa (Suatu Kajian Literatur) - Hado Hado; Ferima Ferima; Maudhy Satyadharma; Muhammad Yazir Jabbar; Muhamad Faza Almaliki; Try Sugiyarto Soeparyanto (Journal of Science, Technology, and Innovation, 2026)
The primary issue in port parking management lies in the imbalance between parking capacity and the increasing volume of vehicles, which leads to congestion, prolonged waiting times, and a decline in service quality and user satisfaction. This study aims to analyze the optimization of port parking management through the implementation of Intelligent Transportation Systems (ITS) based on a literature review approach. The method employed is a narrative literature study involving the collection, selection, and synthesis of relevant scientific sources, including reputable journals, books, and regulatory frameworks. The findings indicate that the implementation of ITS, including parking sensors, real-time information systems, and service digitalization, significantly improves parking management efficiency, reduces space-search time, and enhances traffic flow. The discussion reveals that ITS integration affects not only operational performance but also substantially improves service quality and user satisfaction. This study confirms that the transformation toward smart parking systems represents a strategic step in achieving modern, efficient, and sustainable port services.